The smart archive management practicing pipeline: a virtual online learning platform for AI literacy development in archival science - Lanxi Dong; Shuning Tang; Yuan Cheng; Ping Wang (Information Research: An International Electronic Journal)
Introduction. In order to develop AI literacy for Chinese students majoring in archival science, this study presents the design and implementation of the Smart Archival Learning Platform (SAMPP), providing an immersive environment to understand AI-driven archival workflows, develop AI skills, and improve AI competence.